THE INFLUENCE OF TEACHER PROFESSIONALISM AND LEARNING FACILITIES ON ACHIEVEMENT LEARNING STUDENTS - Rukini Rukini; Jusman Jusman (Jurnal Madako Education, 2020)
This research is a quantitative study to determine how much influence the professionalism of teachers and learning facilities has on the learning achievement of fourth grade students of SDN 03 Tolitoli in the 2016/2017 academic year. The population of this study were 111 students of SDN 03 Tolitoli. The sample used is class IV which amounted to 12 students. The data collection method used a questionnaire and documentation. Data analysis used multiple regression analysis with the help of the SPSS release 16 program. The results showed that multiple linear regression analysis obtained the equation Y = 10,570 + 0.531 + 0.412 + e. F test obtained Fcount = 20.658, so it is accepted. Partially (t test) variable of teacher professional influence obtained t = 2.592, so that be accepted. The learning facility variable obtained tcount = 3.459, so it was accepted. Simultaneously () the professional influence of teachers and learning facilities has an effect on student achievement by 35.7%.  The results of the above research, it can be concluded that there is a significant influence between professional teachers and learning facilities on the learning achievement of fourth grade students of SDN 03 Tolitoli, either simultaneously or partially.Keywords: Teacher Professionalism, Learning Facilities, Student Achievement